IMPLEMENTATION OF THINK TALK WRITE (TTW) TO IMPROVE STUDENT’S ACTIVITY AND LEARNING ACHIEVEMENT - Dian Purnama Sari; Habibi Habibi; L. Habibburahman (Universitas Pendidikan Mandalika, 2016)
This research was aimed to know to improve the aktivities and achievement stundents’ at the VIII-F class of SMPN 11 Mataram of the material optics in learning about Think Talk Write (TTW). This research was used Classroom Action Research (CAR). In this research was action cycle II to students VIII-F class of SMPN 11 Mataram, which consist of 30 students. The result in this research in cycle I was 55,55% which categories enough, although to cycle II was 72.22% which categories anough, the scores of observation in teach by teacher in cycle I was 77,27% which categories good, in cycle II was 90,90% which catergories good. The mean of the students achievement in cycle I was 78 which classical completeness was 73,33%, in cycle II was 86 which classical completeness 86,66%. Therefore, based on the research can be concluded that there learning model Think Talk Write (TTW) in the material optics can improve aktivities and students achievement at the VIII-F class of SMPN 11 Mataram in academic year 2015/2016.